Market Mechanism and Consumer Choice: An Interview with Sophie Dubuisson-Quellier - Dubuisson-QuellierSophie (Journal of Economic Sociology, 2015)
The following conversation with Sophie Dubuisson-Quellier took place during the 12th Conference of the European Sociological Association (Prague, Czech Republic, August 25−28, 2015), where Sophie chaired a session called “Food: Meals and Eating Patterns.” With her colleague Gojard Séverine (French National Institute for Agricultural Research), she presented research on food waste called “Food Waste: from Household Coordination to Cooking Competencies”. In her interview, Sophie shared her research interests and described her recent papers which deal with many aspects of consumer behavior. Sophie illustrates the way social movement organizations interfere in market mechanisms, reshaping the relations between producers and consumers and putting pressure on companies. She also outlined the most common social norms concerning food consumption and discussed possible sanctions for not adhering to them. Sophie describes how patterns of food consumption vary with regard to an individual’s income level, socio-economic class and particular stage in the life course. Further, she clarifies the agenda of modern fair-trade organizations and their role in distribution across markets. Finally Sophie shares her views on urgent topics in modern economic sociology, as well as recommends several readings on the sociology of consumption which may be helpful for those interested in this sphere.